Celiac crisis with thrombocytopenia and coagulopathy in a child - Mazman, Duygu İskender; Dereci, Selim; Hızlı, Şamil; Doğan, Hayriye Tatlı; Ateş, Burcu Berberoğlu; Hızal, Gülin; Demir, Arzu Meltem; Aksu, Aysel Ünlüsoy (The Turkish Journal of Pediatrics, 2022)
Background. Celiac disease rarely presents with edema, hypoalbuminemia, acute metabolic deterioration, and electrolyte imbalances. This life-threatening condition is defined as a celiac crisis and may mimic disorders with metabolic derangement and sepsis. The crisis may present at onset or develop in celiac disease patients with poor compliance to a gluten-free diet. The fluid resuscitation and replacement of electrolyte deficits are life-saving modalities. Case. A 14-month-old girl was admitted with fever, lethargy, severe dehydration, edema, hypotension, and commenced sepsis therapy. However, the patient had a growth delay and loss of weight with diarrhea and delayed motor skills. On admission, laboratory evaluation showed anemia, coagulopathy, hypoalbuminemia, electrolyte disturbances, and metabolic acidosis and developed thrombocytopenia during follow-up. The celiac serological tests and upper gastrointestinal endoscopic duodenal mucosa appearance, and duodenum histopathology findings suggested celiac disease. Conclusions. This case highlights that a celiac patient may present with a severe illness like sepsis and may be associated with cytopenia and coagulopathy in the celiac crisis.
Keywords: celiac crisis; coagulopathy; thrombocytopenia